A Longitudinal Study on Substance Use and Related Problems in Women in Opioid Maintenance Treatment from Pregnancy to Four Years after Giving Birth. (January 2014) - Lund, Ingunn O.; Brendryen, Håvar; Ravndal, Edle
Background: Women in opioid maintenance treatment (OMT) have a past characterized by drug abuse, which is a challenging start for parenthood. Studies of mothers in OMT are typically limited to pregnancy and early infancy. Knowledge about how they cope with substance use and related problems in the years following birth is therefore important. The aims of the study were to examine changes in mothers' substance use, psychological problems, and other challenges; from one to four years after their children were born, and describe kindergarten attendance and prevalence and type of child protective services involvement when the children were four years old. Method: A four-year prospective cohort study of mothers in OMT. The European severity index was used to map substance use and related problems during the third trimester of pregnancy, one and four years after birth. Results: At the four-year follow-up, use of illegal substances remained low (4%) and use of legal substances (39%) was similar to the one-year follow-up. The proportion of women with psychological problems was significantly higher than at one-year follow-up (69 vs. 39%, P = .009). At age four, most children (89%) attended kindergarten, and the child protective services were following 73% of the families, mostly with voluntary measures. Conclusion: Mothers in OMT cope well with substance use over time, given access to sufficient support. The findings imply that a preventive governmental strategy with close support of mother and child, have a positive impact contributing to making OMT and motherhood more compatible.